2004
DOI: 10.1097/00005131-200405000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Evaluation of Methods of Distal Humerus Fracture Fixation Using Locking Compression Plates Versus Conventional Reconstruction Plates

Abstract: The biomechanical behavior of the osteosynthesis depends more on plate configuration than plate type. Advantages of locking compression plates are only significant if compared with dorsal plate application techniques. Nevertheless, locking compression plates are helpful supplementary tools for achieving primary stable fracture fixation. This might be of considerable clinical relevance in patients with diminished bone mineral quality or in the presence of metaphyseal comminution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
133
2
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(151 citation statements)
references
References 35 publications
2
133
2
10
Order By: Relevance
“…11,[13][14][15][16][17][18] No study to date has addressed the issue of biomechanical stability on the transition of the distal humeral diaphysis into the distal segment of the humerus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,[13][14][15][16][17][18] No study to date has addressed the issue of biomechanical stability on the transition of the distal humeral diaphysis into the distal segment of the humerus.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies are very uneven: with regard to the number and types of models, methods and load directions, methods and precision of displacements measurements, and thus the conclusions derived from them are hardly mutually comparable. 11,[13][14][15][16][17][18] Using the finite element method, attempts were made to find the optimal plate configuration which would improve its biomechanical properties, taking into account the specific anatomy of the distal humerus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double-plating techniques using two 3.5-mm plates in orthogonal (90-90) or parallel (180°) patterns are generally accepted. Standard singleplating techniques typically fail to achieve adequate stabilisation [6][7][8]. Yet despite good functional results, nonunions and infections do occur with double-plating techniques [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In a biomechanical study, Korner et al demonstrated that both two standard reconstruction plates and two pre-contoured locking plates provide adequate fixation in an extra-articular distal humerus model [7]. They showed, however, that the locking plate construct provided enhanced stiffness against anterior-posterior bending and torsional loads.…”
Section: Introductionmentioning
confidence: 99%